Structural Analysis and Aggregation Propensity of Pyroglutamate Aβ(3-40) in Aqueous Trifluoroethanol - Dammers, Christina (PLoS One, 2015)
A hallmark of Alzheimer’s disease (AD) is the accumulation of extracellular amyloid-β (Aβ) plaques in the brains of patients. N-terminally truncated pyroglutamate-modified Aβ (pEAβ) has been described as a major compound of Aβ species in senile plaques. pEAβ is more resistant to degradation, shows higher toxicity and has increased aggregation propensity and β-sheet stabilization compared to non-modified Aβ. Here we characterized recombinant pEAβ(3–40) in aqueous trifluoroethanol (TFE) solution regarding its aggregation propensity and structural changes in comparison to its non-pyroglutamate-modified variant Aβ(1–40). Secondary structure analysis by circular dichroism spectroscopy suggests that pEAβ(3–40) shows an increased tendency to form β-sheet-rich structures in 20% TFE containing solutions where Aβ(1–40) forms α-helices. Aggregation kinetics of pEAβ(3–40) in the presence of 20% TFE monitored by thioflavin-T (ThT) assay showed a typical sigmoidal aggregation in contrast to Aβ(1–40), which lacks ThT positive structures under the same conditions. Transmission electron microscopy confirms that pEAβ(3–40) aggregated to large fibrils and high molecular weight aggregates in spite of the presence of the helix stabilizing co-solvent TFE. High resolution NMR spectroscopy of recombinantly produced and uniformly isotope labeled [U-(15)N]-pEAβ(3–40) in TFE containing solutions indicates that the pyroglutamate formation affects significantly the N-terminal region, which in turn leads to decreased monomer stability and increased aggregation propensity.